Rat Strain and Housing Conditions Alter Oxidative Stress and Hormone Responses to Chronic Intermittent Hypoxia - Snyder, Brina; Duong, Phong; Tenkorang, Mavis; Wilson, E. Nicole; Cunningham, Rebecca L. (Frontiers in Physiology, 2018)
Sleep apnea has been associated with elevated risk for metabolic, cognitive, and cardiovascular disorders. Further, the role of hypothalamic–pituitary–adrenal (HPA) activation in sleep apnea has been controversial in human studies. Chronic intermittent hypoxia (CIH) is a rodent model, which mimics the hypoxemia experienced by patients with sleep apnea. Most studies of CIH in rats have been conducted in the Sprague Dawley rat strain. Previously published literature suggests different strains of rats exhibit various responses to disease models, and these effects can be further modulated by the housing conditions experienced by each strain. This variability in response is similar to what has been observed in clinical populations, especially with respect to the HPA system. To investigate if strain or housing (individual or pair-housed) can affect the results of CIH (AHI 8 or 10) treatment, we exposed individual and pair-housed Sprague Dawley and Long-Evans male rats to 7 days of CIH treatment. This was followed by biochemical analysis of circulating hormones, oxidative stress, and neurodegenerative markers. Both strain and housing conditions altered oxidative stress generation, hyperphosphorylated tau protein (tau tangles), circulating corticosterone and adrenocorticotropic hormone (ACTH), and weight metrics. Specifically, pair-housed Long-Evans rats were the most sensitive to CIH, which showed a significant association between oxidative stress generation and HPA activation under conditions of AHI of 8. These results suggest both strain and housing conditions can affect the outcomes of CIH.